Paid Killing in Costa Rica: A Sociological Exploration - Calderón Umaña , Rodolfo (2025)
The study analyzes the characteristics of paid killing in Costa Rica, addressing a phenomenon that has received little attention in the national academic literature. Using a novel approach that examines multiple actors and their complex relationships, the study moves beyond a focus solely on economic ties between intellectual and material perpetrators. Methodologically, it utilizes judgment of convictions, an unexplored data source that provides exclusive information and mitigates security risks. The findings identify two main categories of paid killing: those linked to criminal networks and those arising from conflicts among non-criminal actors. Both categories share characteristics such as a predominance of male perpetrators and the use of firearms, though they differ in aspects like criminal history and involvement of victims and perpetrators in illicit activities. These findings underscore the complexity of the phenomenon and highlight the need to address both its shared and distinctive elements to design effective interventions.